The Role of Transformational Leadership in Enhancing Employee Creativity and Performance: A Social Cognitive Theory Perspective - Utami, Hamidah Nayati; Safira, Vepta Putri (University of Merdeka Malang, 2024)
The competitiveness of domestic technology is currently very high over time, which makes companies competitive with each other in increasing digitalization in the organization. Transformational leadership is crucial for companies to enhance employee creativity, especially for state-owned enterprises (SOEs) in the electric energy sector. The purpose of this study was to determine the effect of (1) Transformational leadership on employee creativity, (2) Transformational leadership on employee performance, and (3) Employee creativity on employee performance. The sampling technique used Proportional Random Sampling. The sample used was permanent employees of a state-owned enterprise in the electric energy sector located in Malang City, Indonesia, with 89 employees. Data were obtained from questionnaires. Data analysis techniques using descriptive statistical analysis and Structural Equation Modeling using the SmartPLS. The results showed that there was a significant effect of transformational leadership on employee creativity while transformational leadership on employee performance showed no significant effect. Besides that, employee creativity on employee performance showed a significant effect.